Some properties of various graphs associated with finite groups - Chen, X.Y.; Moghaddamfar, A.R.; Zohourattar, M. (Algebra and Discrete Mathematics, 2021)
In this paper we investigate some properties of the power graph and commuting graph associated with a finite group, using their tree-numbers. Among other things, it is shown that the simple group L₂(7) can be characterized through the tree-number of its power graph. Moreover, the classification of groups with power-free decomposition is presented. Finally, we obtain an explicit formula concerning the tree-number of commuting graphs associated with the Suzuki simple groups.